Religion Interpretations of Sanitary: Quran Surah Al-Mâidah (5): 6 and Covid 19 Issue: QURAN SURAH AL-MÂIDAH (5): 6 AND COVID 19 ISSUE - Zainal Arifin (Fakultas Ushuluddin Adab dan Humaniora (FUAH), Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto, 2022)
The study of Piwko showed that the greater the religiosity in Islam, the lower the acceptance of pandemic restrictions. Is this issue true? On the other hand, the Quran Surah al-Mâidah (5): 6 became the inspiration for a long study by the commentators in the chapter of Taharah in Islamic Law. The object of this paper will examine the COVID 19 issue and the verse from the sanitation side. This paper uses library research, with the approach of Tafseer Maudûi, the tahlîli system, and also inductive and deductive methods. Conclusion, first, cleanliness and purification are part of Islamic teachings and inseparable from faith and love. Second, ablution and ghusl are the cleanliness, and are very healthy from a medical point of view. Third, although tayammum uses earth, it seems less clean, but in fact earth is clean, purify, and it can be used as a health medium. Fourth, the three advantages of taharah. Fifth, to be grateful that Islamic sanitary starts from personal hygiene, maintaining chastity, continues to maintain the sanctity of prayer places, to maintaining environmental cleanliness. The novelties are that sanitary in the Qur'an is not only limited to a global or general strategy, but is also tactically regulated in a more technical and detailed form. The sanctity and cleanliness of mosques and Muslims is proof that they are not part of the COVID 19 cluster. That the greater the religiosity, the higher the acceptance of cleanliness and purification which can limit the pandemic restrictions. As the message of QS al-Mâidah [5]: 6.